Influence of Online Transportation Applications on Engineering Students' Travel Patterns - Aqlima Putri; Ucha Arief Pratama; Sugiarto Sugiarto; Defry Basrin (Journal of Civil Engineering and Planning (JCEP), 2026)
The advancement of digital technology has significantly transformed urban transportation systems, particularly through the emergence of online transportation applications such as Gojek and Grab. These applications provide more flexible, faster, and easily accessible mobility alternatives for the public, including university students. This study aims to analyze the influence of online transportation application usage on the travel patterns of students at the Faculty of Engineering, Syiah Kuala University, particularly in terms of mode choice, travel frequency, travel time, and trip purpose. The research employs a quantitative approach using a questionnaire survey distributed to students as respondents. The research stages include: (1) primary data collection through questionnaires related to travel characteristics and the use of online transportation applications, (2) data processing using descriptive and statistical analysis to identify travel patterns, and (3) analysis of the relationship between the use of online transportation applications and changes in students’ mobility patterns. The results indicate that the use of online transportation applications significantly influences students’ travel patterns, as reflected by an increase in the frequency of app-based transportation usage, a reduction in dependence on private vehicles, and more flexible travel times and routes. Furthermore, factors such as ease of access, time efficiency, and cost are the main considerations in choosing online transportation modes. This study suggests that the integration of technology into transportation systems can enhance student mobility efficiency and has the potential to support the development of more sustainable urban transportation systems.